2002
DOI: 10.1046/j.1365-2648.2002.02294.x
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of nurses' attitudes and practices regarding brief alcohol intervention in primary health care

Abstract: Background.  Excessive alcohol consumption causes significant mortality, morbidity, economic and social problems in the United Kingdom (UK). Despite strong evidence for the effectiveness of brief intervention to reduce excessive drinking in primary health care, there is little indication that such intervention routinely occurs. Aims.  This study aimed to explore primary health care nurses' attitudes and practices regarding brief alcohol intervention in order to understand why it is underexploited. Methods.  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
124
3
22

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(160 citation statements)
references
References 25 publications
11
124
3
22
Order By: Relevance
“…[21][22][23][24][25] Alcoholism is stigmatized, even among health care providers, 26,27 who may expect patients to object when the topic is raised 1,28,29 and to under-report consumption and problems. 26,30 Anecdotally, we did occasionally field questions from patients about whether their provider thought they were Ban alcoholic.^Thus, a common misconception may be that a doctor would only be concerned about a patient's drinking if there was a suspected AUD. Further education of the medical community and the general public is warranted regarding the effects on medical conditions and disease management, not just AUD, that can result from exceeding the NIAAA threshold for low-risk alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] Alcoholism is stigmatized, even among health care providers, 26,27 who may expect patients to object when the topic is raised 1,28,29 and to under-report consumption and problems. 26,30 Anecdotally, we did occasionally field questions from patients about whether their provider thought they were Ban alcoholic.^Thus, a common misconception may be that a doctor would only be concerned about a patient's drinking if there was a suspected AUD. Further education of the medical community and the general public is warranted regarding the effects on medical conditions and disease management, not just AUD, that can result from exceeding the NIAAA threshold for low-risk alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…On specific information offered during the nursing graduate course, a study done in the late 1990s (18) , revealed among other things that alcohol and drugs were not topics of priority in the formation of nurses. More recent investigations, evaluating the knowledge obtained by nursing graduates, showed that while receiving some specific content they still had difficulty establishing interpersonal relationships with dependents (24)(25) . Acts as a script which orients attention of the professional and helps to better know the patient (define profile, demonstrate characteristics and stages, observation guide, aid in perception).…”
Section: Discussionmentioning
confidence: 99%
“…18 Among a number of barriers to delivering brief intervention, [19][20][21][22] providers have cited concerns that patients may prefer not to discuss their drinking or may react negatively to such conversations. [19][20][21][23][24][25] In other words, providers are concerned that these discussions may compromise their relationships with patients. However, a previous study among general outpatients with unhealthy alcohol use found that those who reported receipt of brief intervention rated their care as higher quality than those not reporting brief intervention.…”
mentioning
confidence: 99%